Edukasi Hidup Sehat Membiasakan Cuci Tangan Sebagai Upaya Pencegahan Penyakit Infeksi Di Era Pandemi Covid - Arleen Devita; Yuliana; Ida Effendi; Meiyanti (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2022)
Rawa Buaya Village is one of the villages in the West Jakarta. This village is a densely populated village with a limited number of health facilities. Based on the 2018 DKI National Basic Health Research (RISKESDAS) data, the proportion of the population aged over 10 years in West Jakarta who behaved properly in washing their hands was only 49.11%. Hand washing is the most important basic technique in the prevention and control of infection transmission because it mechanically removes dirt and dust from the skin surface and reduces the number of pathogenic microorganisms. Because knowledge of clean and healthy living behavior (PHBS) by washing hands with soap is a determining factor in the transmission of infectious diseases such as diarrhea, respiratory infections including Covid-19, education is needed to increase this knowledge. Education by counseling and training activities are carried out online through the Zoom teleconference on April 23, 2022, followed by 45 village residents. Participants' knowledge was assessed by pre-test and post-test using Google Form. From the post-test’s results, there is an increase in the participants’s knowledge by 22.9% with an increase in the percentage of correct answers from the pre and post test ranging from 6.6% - 35.6%, which is also expected to change in habits or behavior.